Analysis of Differences in Hospital Rates and Rates Ina-CBGS Poly Urology Outpatient Services at Mitra Medika Tanjung Mulia Hospital - Muhammad Iqbal; Dede Ruslan; Deli Theo (Journal La Medihealtico, 2021)
In the implementation of the National Health Insurance there are still many problems that arise, one of which is of concern is the tariff for Indonesian Case Based Groups (INA-CBGs). The government is very likely to realize that there is a mismatch between INA-CBGs rates and hospital real costs. The purpose of this study was to determine the difference in hospital rates and INA-CBGs rates for outpatient services at the Urology Poly at Mitra Medika Tanjung Mulia Hospital in January 2019.This type of research is cross sectional with a quantitative approach. The population in this study were all medical record files of outpatient poly urology who underwent treatment at the Mitra Medika Tanjung Mulia Hospital in January 2019. The total sample technique was 310 people.The Wilcoxon test results obtained that the A-Symp Sig (2-tailed) value was 0,000, which means that there is a significant difference between the hospital rate and the INA-CBG outpatient service Urology Poly at Mitra Medika Tanjung Mulia Hospital in January 2019. The conclusion in this study is the difference between the hospital rates and the INA-CBG package rates on the payment of outpatient JKN participant claims at Mitra Medika Hospital lies in the standard rates applied. It is expected that the hospital staff can evaluate the calculation of unit costs for each service unit service. Outpatient care, especially in the poly urology service division, which experienced a negative rate difference so that the hospital suffered a loss.